Antecedents of Individuals' Concerns Regarding Hospital Hygiene and Surgery Postponement During the COVID-19 Pandemic: Cross-sectional, Web-Based Survey Study - Ostermann, Thomas; Gampe, Julia; Röer, Jan Philipp; Radtke, Theda (JMIR Publications, 2021)
BackgroundThe COVID-19 pandemic poses a major challenge to people's everyday lives. In the context of hospitalization, the pandemic is expected to have a strong influence on affective reactions and preventive behaviors. Research is needed to develop evidence-driven strategies for coping with the challenges of the pandemic. Therefore, this survey study investigates the effects that personality traits, risk-taking behaviors, and anxiety have on medical service-related affective reactions and anticipated behaviors during the COVID-19 pandemic. ObjectiveThe aim of this study was to identify key factors that are associated with individuals' concerns about hygiene in hospitals and the postponement of surgeries. MethodsWe conducted a cross-sectional, web-based survey of 929 residents in Germany (women: 792/929, 85.3%; age: mean 35.2 years, SD 12.9 years). Hypotheses were tested by conducting a saturated path analysis. ResultsWe found that anxiety had a direct effect on people's concerns about safety (β=−.12, 95% CI −.20 to −.05) and hygiene in hospitals (β=.16, 95% CI .08 to .23). Risk-taking behaviors and personality traits were not associated with concerns about safety and hygiene in hospitals or anticipated behaviors. ConclusionsOur findings suggest that distinct interventions and information campaigns are not necessary for individuals with different personality traits or different levels of risk-taking behavior. However, we recommend that health care workers should carefully address anxiety when interacting with patients.